2006
DOI: 10.1111/j.1745-7262.2006.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosomal microdeletions and partial deletions of the Azoospermia Factor c (AZFc) region in normozoospermic, severe oligozoospermic and azoospermic men in Sri Lanka

Abstract: These results suggest that the frequency and pattern of microdeletions of the Y chromosome in Sri Lankan men are similar to those found in other populations and confirm that gr/gr deletions are not sufficient to cause spermatogenetic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
6
28
0
Order By: Relevance
“…The frequency of the gr/gr deletions in infertile Caucasian males has been reported to be in the range of 3.2% to 5% [Giachini et al 2008;Navarro-Costa et al 2007;Stouffs et al 2008]. The findings of this study are also in agreement with that of others de Carvalho et al 2006;Fernando et al 2006;Hucklenbroich et al 2005;Imken et al 2007;Lardone et al 2007;Lin et al 2007;Lu et al 2009;Ravel et al 2009;Stouffs et al 2008;Wu et al 2007;Zhang et al 2007] that showed no association of gr/gr deletions in infertile males. However, the results of this study differ from the findings of Repping et al [2003] and de Llanos et al [2005] which showed an association of gr/gr deletions in male infertility (P value of < 0.014 and 0.002, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of the gr/gr deletions in infertile Caucasian males has been reported to be in the range of 3.2% to 5% [Giachini et al 2008;Navarro-Costa et al 2007;Stouffs et al 2008]. The findings of this study are also in agreement with that of others de Carvalho et al 2006;Fernando et al 2006;Hucklenbroich et al 2005;Imken et al 2007;Lardone et al 2007;Lin et al 2007;Lu et al 2009;Ravel et al 2009;Stouffs et al 2008;Wu et al 2007;Zhang et al 2007] that showed no association of gr/gr deletions in infertile males. However, the results of this study differ from the findings of Repping et al [2003] and de Llanos et al [2005] which showed an association of gr/gr deletions in male infertility (P value of < 0.014 and 0.002, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…2,6,33,34 In this study, we found an increased prevalence of AZFc partial deletions (11.87%) in infertile men compared with normozoospermic fertile men, suggesting that such mutations represent a risk factor for male infertility. Among these partial AZFc deletions, there were 30 cases with gr/gr subtype, 16 with b1/b3 and 6 with b2/b3.…”
Section: Discussionmentioning
confidence: 72%
“…36 However, other studies have reported very low frequencies of these subdeletions and found no association with infertility and/or spermatogenesis. 14,16,19,27,34,37 Either genetic background of the population studied or the type of infertility might explain the reasons in the frequencies of the different subdeletions.…”
Section: Discussionmentioning
confidence: 99%
“…An association between AZFc subdeletions and severe spermatogenic failure (SSF) was observed in several populations, including Australian, European, Han-Chinese, Moroccan, and North Indian populations (Navarro-Costa et al, 2007;Lu et al, 2009;Shahid et al, 2011;Bunyan et al, 2012;Eloualid et al, 2012). However, screening studies in several other populations contradict these findings (Machev et al, 2004;Hucklenbroich et al, 2005;Fernando et al, 2006). Furthermore, the estimated frequency of AZFc subdeletions reported in various population studies is not consistent with each other.…”
Section: Introductionmentioning
confidence: 86%